2002
DOI: 10.1179/030192302225005196
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of ladle glaze interactions

Abstract: model with particular emphasis on the incorporation of ladle glaze, which has been identi ed as a potential source A potential source of inclusions in liquid steel is of inclusions of variable, often undesirable, composition. A ladle glaze, the slag/inclusion coating on the description of pilot plant experiments that were carried out refractory lining of the ladle which is always present to determine the eVect of tapping operations on ladle glaze after casting and before reuse of the ladle. The is given, toget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 3 publications
1
32
0
Order By: Relevance
“…The ladle lining (refractory) in their study was magnesite refractory (carbon-bearing MgO lining). Riaz et al 7) and Hassall et al 8) also performed similar studies on the plant ladle treatment with magnesite refractory. The primary concerns of previous studies were to identify the inclusions and to correlate the melt cleanliness (the number of inclusion) and ladle age.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…The ladle lining (refractory) in their study was magnesite refractory (carbon-bearing MgO lining). Riaz et al 7) and Hassall et al 8) also performed similar studies on the plant ladle treatment with magnesite refractory. The primary concerns of previous studies were to identify the inclusions and to correlate the melt cleanliness (the number of inclusion) and ladle age.…”
Section: Introductionmentioning
confidence: 69%
“…The feasibility of the physical detachment can be supported by the microstructure of the glaze layer showing the existence of spinel particles on the interface of glaze and molten steel. Several previous studies [7][8][9][10][11] for the ladle glaze of a magnesite lining also suggested that the particles like MgO originally formed in the glaze layer can be retained in the liquid steel as inclusions. For example, Beskow and Du Sichen 10) reported that the complex inclusion of liquid CaO-Al 2 O 3 (-MgO-SiO 2 ) bearing MgO particles, one of the typical inclusions in a practical ladle treatment, was most probably originated from the ladle glaze itself.…”
Section: Molten Steel and Inclusionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] Erosion experiments that immersed lining samples into a melt (steel melt [148][149][150][151] or Fig. 29-Effect of teeming rate on the free surface of steel entering a bottom-poured 8-in.…”
Section: Slag Properties Such As Interfacial Tensionmentioning
confidence: 99%
“…Lining refractory [89,[148][149][150][151][152][153] Analysis of the lining refractory composition before and after operations can be used to estimate inclusion absorption to the lining and the lining erosion. Also, the origin of a complex oxide inclusion can be traced to lining refractory erosion by matching the mineral and element fractions in the slag with the inclusion composition.…”
Section: Slag Composition Measurementmentioning
confidence: 99%